Use of mixed Indonesian-Patani language codes in oral form by Patani (South of Thailand) pupils in Medan City - Salae, Asuepan; Kartolo, Rahmat; Sutikno (International Journal of Educational Research Excellence (IJERE), 2024)
This research examines code mixing among Patani students in Medan City. The study aims to describe, analyze, interpret, and conclude data on the use of Indonesian-Patani code mixing in oral form by Patani students from southern Thailand in Medan City, focusing on the lexicon form of code mixing. This research aims to investigate code mixing in the interactions of Patani students in the city of Medan. The data was collected using recording and note-taking techniques. The transcribed data was classified, analyzed, and interpreted to draw conclusions. Data analysis results indicate that Patani students in Medan City code-mix verbs, adjectives, nouns, pronouns, numerals, adverbs, and task words. In the research, the causes of code-mixing are divided into four categories: (i) a continued focus on the mother tongue, especially Patani Malay, (ii) difficulty in interacting with an environment that uses both Indonesian and regional languages, (iii) a lack of understanding of Indonesian, resulting in incorrect pronunciation, and (iv) difficulty in understanding new Indonesian vocabulary, resulting in the combination of familiar languages.